PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN KOMPETENSI PEDAGOGIK TERHADAP MUTU SEKOLAH DI SMA SE-KECAMATAN PEKALONGAN LAMPUNG TIMUR - Reziki, Yunia Sari; Dacholfany, M. Ihsan (Lembaga Penelitian UM Metro, 2018)
This research aims to determine the influence of principalâ??s academic supervision on the quality of the school, the influence of pedagogical competence on the school quality, and the influence of principalâ??s academic supervision and pedagogical competence collectively to the quality of the school in Senior High School in East Lampung Pekalongan District.The approach in this research is quantitative approach, there are three variables, namely the academic supervision (X1), the pedagogik competence (X2), and the school quality (Y). The population in this research is 79 teachers, while the sample in this research is 44 teachers. The main method of collecting data used is questionnaire or questionnaire. Data analysis techniques in this study using simple linear regression analysis and multiple regression analysis.